Pengukuran Tingkat Kapabilitas Tata Kelola Teknologi Informasi Menggunakan Framework Cobit 5 dan Rekomendasi Perbaikan (Studi Kasus: Badan Pengembangan Teknologi Informasi) - Rizky Sugiharti Utami (Jurnal EMT KITA, 2021)
This study aims to measure the level of IT Governance capability and provide recommendations for improving IT Governance in Information Technology Development Institute using COBIT 5. The domains chosen in this research are APO and BAI in order to improve IT services and optimize IT implementation in BPTI environment. The research method used are interviews and questionnaires in obtaining research data. Based on the results of the study, it was found that the measurement of the eight selected processes indicated that most of the processes were already at level 1, and a few were at level 0. Based on the results of prioritization, the process that became the top priority in making improvements was APO07, namely Managing Human Resources. This research was only carried out in eight processes which were in accordance with previously mapped, so that this research was more complete and comprehensive, it could be carried out using other process areas in COBIT 5.